Health literacy and knowledge in a cohort of Australian patients taking warfarin - Yiu AW; Bajorek BV (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objectives: To 1) characterise older patients taking warfarin, 2) assess these patients' level of warfarin knowledge, and 3) describe their strengths and limitations in health literacy, and 4) explore relationships between participants' characteristics, warfarin knowledge and health literacy. Methods: A warfarin knowledge questionnaire and Health Literacy Questionnaire (HLQ) were administered to older patients (aged >65 years, N=34) taking warfarin in an Australian general practice setting. Results: Key gaps in participant knowledge pertained to the consequences of an international normalized ratio (INR) being below the target INR range and safety issues such as when to seek medical attention. A limitation for participants with a lower level of health literacy was the ability to appraise health information. Patients who needed assistance in completing the HLQs had significantly lower warfarin knowledge scores (p=0.03). Overseas-born participants and those taking 5 or more long-term medications had lower HLQ scores for specific scales (p<0.05). Conclusion: In this study warfarin knowledge gaps and a limitation of health literacy amongst a small sample of older patients were identified. The findings suggest that education and resources may need to be tailored to the needs of older patients taking warfarin and their carers to address these knowledge gaps and limitations in health literacy. Patients who may need greater support include those that need assistance in completing the HLQ, are overseas-born, or are taking 5 or more long-term medications.